Cloning and expression analysis of the Hsp70 gene ZmERD2 in Zea mays. Issue 2 (3rd March 2016) - Song, Jinhui; Weng, Qiaoyun; Ma, Hailian; Yuan, Jincheng; Wang, Lingyun; Liu, Yinghui
ABSTRACT: In this study, an Hsp70 gene was isolated from maize and was designated as ZmERD2 (Early Responsive to Dehydration 2). The full cDNA sequence of ZmERD2 was 2375 bp. It includes a 1949 bp open reading frame (ORF) encoding 649 amino acids. The calculated molecular mass was 71.163 kDa. The protein encoded by ZmERD2 contains an Hsp70 conservative structure domain, three typical Hsp70 family signature sequences and a cytosolic Hsp70-specific motif, which belongs to the Hsp70 family. Phylogenetic tree analysis suggested that ZmEDR2 shares high similarity (92%–95%) with Hsp70 of other plants, such as Arabidopsis thaliana (NP 195870), Triticum urartu (EMS52605), Aegilops tauschii (EMT07406) and Nicotiana tabacum (AAR17080), and was clustered together with T. urartu and A. tauschii . The promoter of ZmERD2, which was located at about 2.2 kb upstream of ZmERD2, was cloned and was predicted to contain important regulatory elements, including TATA-box, CAAT-box and drought-, heat-, cold-, salicylic acid- and methyl jasmonate-responsive elements. Analyzed by quantitative real-time polymerase chain reaction, the expression of ZmERD2 in maize was induced by heat, high-salt, cold, polyethylene glycol, heat stress and dehydration treatments, but not by abscisic acid. The expression of ZmEDR2 was quickly induced at 42 °C and reached its peak after 1 h of heat stress, with an expression of 40-fold above the control level. These results suggested that ZmERD2 might be a stress-related gene in maize.